Influence of Electrodes Configuration on Metallized Film Capacitor Performance Metrics - Belko V.O.; Cheng Lu; Kalmykova S.I.; Pechnikov A.V.; Plotnikov A.P. (Problems of the Regional Energetics)
The aim of the study is to reveal the influence of the electrode configuration of metallized film capacitors on their characteristics and performance under conditions typical of power electron-ics. Presently used electrodes configurations are summarized, their benefits and disadvantages are analyzed. We showed that currently used metallized film capacitors electrodes configura-tions, ensuring reliable self-heling, have too high equivalent resistivity. Authors propose to in-troduce a hybrid type of electrode for metallized film capacitors. We showed the influence of the capacitor electrodes on its performance under the conditions typical of power electronics and experimentally studied the effect of the electrode thickness on the breakdown strength. The breakdown strength of polymer films with various metallization thickness was determined using common dielectric testing methodology. We found out that the breakdown strength follows Weibull distribution and slightly depends on vacuum sputtered metal thickness, unlike previous studies results. The effects from the fracture of electrodes caused by electrical discharges occur-ring during self-healing of metallized film capacitors are demonstrated experimentally. It was established the prominent influence of electrical explosion and micro-arc destruction of metal-lized electrode on polymer film breakdown strength. The results of numerical and analytical cal-culations of equivalent electrode resistivity for various configurations are presented. Compara-tive calculations of the surface resistance and active area of segmented and hybrid electrodes showed the advantage of the latter. We experimentally established that at comparable process durations the deposited energy for the fracture of hybrid electrodes was less than for segmented ones.